2012
DOI: 10.3797/scipharm.1208-10
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Stability-Indicating RP-HPLC Method for Determination of Rupatadine and its Degradation Products in Solid Oral Dosage Form

Abstract: A simple, sensitive, and reproducible reversed-phase high-performance liquid chromatography (RP-HPLC) method, coupled with a photodiode array detector, was developed for the determination of rupatadine (RUPA) and its related substances in pharmaceutical dosage forms. Chromatographic separation was achieved on the Hypersil BDS (150 x 4.6 mm, 5 μm) column with a mobile phase containing a gradient mixture of a buffer (acetate buffer pH-6.0) and solvent (methanol). The eluted compounds were monitored at 264 nm for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…There are different methods to identify and quantify LOR and RUP in pharmaceutical preparations and biological tissue. LOR (El Ragehy, Badawey, Khateeb, 2002;Rupérez, Fernández, Barbas, 2002;Radhakrishna et al, 2003;Ulavapalli et al, 2011) and RUP (Nogueira et al, 2008;Trivedi, Patel, 2012) were determined or quantified by HPLC. Capillary electrophoresis (CE) was also used as a method to determine LOR (Rambla-Alegre et al, 2010;El-Awady, Belal, Pyell, 2013;Hancu et al, 2014) and RUP (Nogueira et al, 2008).…”
Section: Instrumentationmentioning
confidence: 99%
“…There are different methods to identify and quantify LOR and RUP in pharmaceutical preparations and biological tissue. LOR (El Ragehy, Badawey, Khateeb, 2002;Rupérez, Fernández, Barbas, 2002;Radhakrishna et al, 2003;Ulavapalli et al, 2011) and RUP (Nogueira et al, 2008;Trivedi, Patel, 2012) were determined or quantified by HPLC. Capillary electrophoresis (CE) was also used as a method to determine LOR (Rambla-Alegre et al, 2010;El-Awady, Belal, Pyell, 2013;Hancu et al, 2014) and RUP (Nogueira et al, 2008).…”
Section: Instrumentationmentioning
confidence: 99%
“…Several analytical methods have been reported for RUP determination either alone or in combination with other drugs. such as spectrophotometry [6][7][8][9][10], spectrofluorimetry [11,12], HPTLC [13][14][15], micellar electrokinetic chromatography [16], and HPLC methods [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Several stability-indicating assay methods have been reported for RUP determination as summarized in Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review revealed that most reported HPLC methods for RUP determination incorporate more than one organic modifier with a very high organic % that reaches 90% v/v in some methods [1719, 21, 23, 25, 26, 2830]. Some methods use heptane sulfonic acid for RUP ion pairing [27], and some use polar cyano‐column [29]or less nonpolar C8 column [17] or incorporate gradient elution with increasing organic ratio within the run [20, 24].…”
Section: Introductionmentioning
confidence: 99%
“…[ 8–12 ] Conversely, several chromatographic methods with various detection patterns have been reported to determine rupatadine. [ 13–24 ] Chromatographic techniques require large volumes of hazardous organic solvents, tedious procedures, sometimes need expensive detectors and have lengthy procedures. Spectroscopic techniques are frequently used in laboratories to characterize or quantify medicines.…”
Section: Introductionmentioning
confidence: 99%